2011
DOI: 10.1016/j.molcel.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Ras-Induced Expression of Noxa and Beclin-1 Promotes Autophagic Cell Death and Limits Clonogenic Survival

Abstract: Deregulated oncogenes such as MYC and RAS are typically insufficient to transform cells on their own due to the activation of pathways that restrain proliferation. Previous studies have shown that oncogenic H-Ras can induce proliferative arrest or senescence, depending on the cellular context. Here, we show that deregulated H-Ras activity can also lead to caspase-independent cell death with features of autophagy. Ras-induced autophagy was associated with upregulation of the BH3-only protein Noxa as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
322
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 374 publications
(347 citation statements)
references
References 29 publications
17
322
3
5
Order By: Relevance
“…Considering the emerging role of Mcl-1 in mediating starvation-induced autophagy 10,11,24 , we first assessed the contribution of endogenous Mcl-1 to the regulation of basal, housekeeping autophagy. Protein levels of Mcl-1, Bcl-2 or Bcl-xL were depleted by transiently transfecting 293T cells with two different siRNAs against each protein or a control siRNA against Luciferase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the emerging role of Mcl-1 in mediating starvation-induced autophagy 10,11,24 , we first assessed the contribution of endogenous Mcl-1 to the regulation of basal, housekeeping autophagy. Protein levels of Mcl-1, Bcl-2 or Bcl-xL were depleted by transiently transfecting 293T cells with two different siRNAs against each protein or a control siRNA against Luciferase.…”
Section: Resultsmentioning
confidence: 99%
“…However, emerging reports now suggest that Mcl-1 is implicated in other cellular processes that may contribute to its tumorigenic potential. Recently, Mcl-1 has been implicated in the regulation of mitochondrial bioenergetics and morphogenesis 8 , chemotherapy-induced senescence 9 , starvation and Ras oncogene-induced autophagy 10,11 , suggesting that its contribution to tumorigenesis may go beyond evading apoptosis. Targeting Mcl-1 is emerging as a potential therapeutic strategy [12][13][14][15][16] and therefore a deeper understanding of the mechanisms controlling Mcl-1 levels and function is of paramount importance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] The implication of autophagy in oncogenesis has also been debated, some reports indicating a role in tumor persistence, whereas others suggested that it could be a cell death mechanism that, along with proliferative senescence, is a safeguard against excessive or unscheduled proliferative signals. 20,21 In support to that idea, Elgendy et al 22 recently provided an interesting example of 'autophagic cell death' induced by oncogenic H-Ras V12 in a human ovarian surface epithelial cell line.…”
mentioning
confidence: 93%
“…Several reports demonstrated that activation of autophagy may suppress tumor development and lead to cell death. 53,54 However, it has been demonstrated extensively that autophagy mediates tumor survival by supplying nutrients to stressed cancer cells. 55 Therefore, an anti-autophagy approach may also offer a therapeutic strategy for treating cancer.…”
Section: Therapeutic Potential Of Mirnas and Autophagic Pathwaymentioning
confidence: 99%